An Orthotopic Mouse Model of Laryngeal Squamous Cell Carcinoma. (February 2015) - Cohen, Jacob T.; Gil, Ziv; Binenbaum, Yoav; Na'ara, Shorook; Amit, Moran
Objective: This study aimed to create a reliable and reproducible orthotopic mouse model of laryngeal malignancy that recapitulates its biologic behavior, local invasiveness, and spread as seen in patients. Methods: Via direct laryngoscopy, human squamous cell carcinoma line FaDu (ATCC HTB-43) was implanted in the larynx (supraglottis and glottis) in nu/nu mice (n = 31). Animals were monitored with direct laryngoscopy and ultrasound for tumor growth and survival. Specimens of larynxes, neck lymphatics, livers, and lungs were removed for histopathologic evaluation to assess tumor extension, thyroid cartilage invasion, and nodal spread. Results: Thirty-one successful direct laryngoscopies were performed. Supraglottic and glottic tumor uptake was 100% and 25%, respectively. Median survival for the animals with supraglottic tumors was 35 days. Histopathologic evaluation revealed pre-epiglottic extension, paraglottic extension, thyroid cartilage invasion, and lymph node metastasis. Conclusion: We describe the first orthotopic model for laryngeal cancer. Our model faithfully recapitulates the phenotype and malignant behavior that reproduces its natural biologic behavior as seen in laryngeal cancer patients. This model offers an opportunity to identify and specifically target therapy for larynx squamous cell carcinoma.